Memorandum of Understanding between the lnternational Network for the Availability of Scientific Publications and Brac University (2010) ﻿ ﻿ - The lnternational Network for the Availability of Scientific Publications; Brac University (The lnternational Network for the Availability of Scientific Publications and Brac University, 2019)
The agreement made between The international Network for the Availability of Scientific Publications and Brac University for implementing VuFind at Ayesha Abed Library, Brac University.